Twenty-first century glacier slowdown driven by mass loss in High Mountain Asia. Issue 1 (January 2019) - Dehecq, Amaury; Gourmelen, Noel; Gardner, Alex; Brun, Fanny; Goldberg, Daniel; Nienow, Peter; Berthier, Etienne; Vincent, Christian; Wagnon, Patrick; Trouvé, Emmanuel
Abstract Glaciers in High Mountain Asia have experienced heterogeneous rates of loss since the 1970s. Yet, the associated changes in ice flow that lead to mass redistribution and modify the glacier sensitivity to climate are poorly constrained. Here we present observations of changes in ice flow for all glaciers in High Mountain Asia over the period 2000–2017, based on one million pairs of optical satellite images. Trend analysis reveals that in 9 of the 11 surveyed regions, glaciers show sustained slowdown concomitant with ice thinning. In contrast, the stable or thickening glaciers of the Karakoram and West Kunlun regions experience slightly accelerated glacier flow. Up to 94% of the variability in velocity change between regions can be explained by changes in gravitational driving stress, which in turn is largely controlled by changes in ice thickness. We conclude that, despite the complexities of individual glacier behaviour, decadal and regional changes in ice flow are largely insensitive to changes in conditions at the bed of the glacier and can be well estimated from ice thickness change and slope alone. Changes in glacier speed in High Mountain Asia are closely linked to mass balance through gravitational driving stress, and largely insensitive to basal conditions, according to satellite-derived ice-flow observations.